A RETROSPECTIVE ANALYSIS OF WOMEN WITH A COMPLICATED OBSTETRICS ANAMNESIS (World Bulletin of Public Health, 2023)
According to statistics, one of the main reasons of babies death is the birth of a fetus with birth defects. Nowadays, there are more than 4,000 known fetal malformations [3,12]. One of the most common fetal developmental defects is neural tube defects (NTDs), which is registered annually in 300,000 newborns in the world. Many surviving patients with this pathology are counted in disability groups depending on the localization of the spinal defect [2,3,7,8]. Spina bifida may be associated with plegia, bladder and bowel dysfunction, hydrocephalus, and learning disabilities [2,4,5,6,9].